Instant Apache Sqoop : transfer data efficiently between RDBMS and the Hadoop ecosystem using the robust Apache Sqoop /: transfer data efficiently between RDBMS and the Hadoop ecosystem using the robust Apache Sqoop. (2013) - Unknown
No abstract available